2001
DOI: 10.1080/03069880020047157
|View full text |Cite
|
Sign up to set email alerts
|

Emotional competence and willingness to seek help from professional and nonprofessional sources

Abstract: We sought to determine the relationship between emotional competence and willingnes seek help for emotional problems and suicidal ideation. A survey of 300 university undergraduate assessed emotional competence (skill at emotion perception, managing self-relevant emotions, a managing others' emotions), hopelessness, willingness to seek help from health professionals (e counsellor) and nonprofessionals (friends, family), and perceived usefulness of past help-seeking experience. Those who reported feeling less s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 35 publications
2
71
0
3
Order By: Relevance
“…Komiya et al (2000) also found that reluctance to seek psychological services was greater for those less open to their emotions. Similarly, those less skilled at dealing with emotions have also been found to be less likely to seek help, in general, as well as less likely to seek help from a mental health professional for concerns about suicide (Ciarrochi & Deane, 2001). Therefore, those who have experienced a distressing event should be most likely to report concerns about self-disclosing emotional issues to a counselor.…”
Section: Studymentioning
confidence: 99%
“…Komiya et al (2000) also found that reluctance to seek psychological services was greater for those less open to their emotions. Similarly, those less skilled at dealing with emotions have also been found to be less likely to seek help, in general, as well as less likely to seek help from a mental health professional for concerns about suicide (Ciarrochi & Deane, 2001). Therefore, those who have experienced a distressing event should be most likely to report concerns about self-disclosing emotional issues to a counselor.…”
Section: Studymentioning
confidence: 99%
“…Clearly, treatment fears are an important avoidance factor, but more information is needed about their role relative to other factors. Persons who were less skilled at dealing with emotions have also been found to be less likely toseek help, in general, as well as less likely to seek help from a mental health professional for concerns about suicide (Ciarrochi& Deane, 2001). Vogel and Wester (2003) found that expectations of having to express emotions to a therapist affected individuals' help-seeking attitudes and intentions.…”
Section: Blocks In Counselingmentioning
confidence: 99%
“…Finfgeld-Connett (2005) adds factors such as common demographic and sociocultural aspects. Therefore, examples of sources of support are spouses, other family members, colleagues, supervisors, friends, peers, neighbours, church members, support groups, health care professionals, teachers and acquaintances (Ciarrochi & Deane, 2001;Finfgeld-Connett, 2005;Patterson, 2003). Finfgeld-Connett (2005) and Ciarrochi and Deane (2001) draw a distinction between professional and nonprofessional social support.…”
Section: Literature Review the Concept Of Social Supportmentioning
confidence: 99%